Studi Bioaktivitas Antibakteri Fraksi Protein Hidroid Aglaophenia cupressina Dari Pulau Lae-Lae Sulawesi Selatan - Nur Umriani; Abdul Rauf Patong; Ahyar Ahmad (Hasanuddin University, 2008)
This research aimed to know the activity of bioactive protein, extracted from Hydroid (Aglaophenia cuppressina), in inhibiting the growth of pathogenic bacteria. Samples were taken from Lae-lae Island in South Sulawesi. Methods used were the Lowry method for determining the protein concentration and the agar diffusion method for testing the antibacterial activity. Extraction of Hydroid was conducted by making use of buffer solution, (0,1 M Tris-HCl of pH 8.3, 2 M NaCl, 0.01 M CaCl, 1% β-mercaptoethanol, and 0.5% Triton X-100). Protein was purified by ammonium sulfate precipitation at 20%, 40%, 60% and 80% saturation followed by dialysis. Results showed that the protein fraction of Aglaophenia cuppressina before dialysis with 40 % ammonium sulfate saturation had the highest antibacterial activity to Staphylococcus aureus and Escherichia coli with inhibition zones of 14.58 and 18.05 mm, respectively. In addition, the protein fraction of Aglaophenia cuppressina after dialysis with 40 % saturation also had the highest antibacterial activity to the tested bacteria with inhibition zones of 13.95 and 11.78 mm, respectively. The minimum inhibition concentration to the tested bacteria and Escherichia coli at 40% ammonium sulfate (0,1 M Tris-HCl of pH 8.3, 2 M NaCl, 0.01 M CaCl 2 saturation was 6000 µg/mL with inhibition zones of 9.78 and 8.73 mm, respectively. Based on the bioactivity test of the Hydroid protein fraction using the agar diffusion method, it can be concluded that the activity characteristic of the fraction is bacteriostatic.Key words: Bioactivity, hydroid, bioactive protein, antibacterial, inhibition zone.